Inégalités sociales et enjeux liés à la santé des aînés francophones en situation minoritaire : le cas de l’Atlantique et de l’Acadie des Maritimes - Simard, Majella; Bouchard, Louise (Organisations & Territoires, 2020)
Le vieillissement démographique soulève des enjeux fondamentaux dans la réponse des acteurs sociaux aux besoins manifestés par les aînés sur le plan de la santé. L’objectif de cette contribution est double. Il consiste, d’une part, à identifier les principaux enjeux auxquels sont confrontés les aînés francophones en situation minoritaire sur le plan de la santé et, d’autre part, à examiner la situation des inégalités sociales et les conditions de vie qui en découlent comme déterminant de la santé, de la qualité et de l’accès aux services dans une perspective de développement territorial. Les résultats de notre analyse révèlent que le rapport minoritaire/ majoritaire traduit une inégalité sociale qui, couplée à d’autres déterminants sociaux, contribue de facto à la formation de disparités sur le plan de la santé, d’où la nécessité de mettre en oeuvre une politique à l’endroit des aînés vivant en milieu minoritaire francophone destinée à réduire de tels écarts.

État des connaissances sur la santé et les services de santé aux aînés francophones en contexte linguistique minoritaire - Bouchard, Louise; Savard, Jacinthe; Renaud, Alexandre (Reflets, 2022)
La recherche en santé sur les communautés de langue officielle en situation minoritaire (CLOSM) a connu un essor remarquable ces deux dernières décennies. L’objectif de cet article est de présenter un état des lieux de la recherche effectuée sur la problématique de la santé et des soins destinés aux personnes âgées francophones en situation linguistique minoritaire. Différents thèmes sont abordés tels que la santé et ses déterminants, l’expérience des usagers quant à la langue des services, l’environnement légal et politique des services en français, l’organisation des services et la performance du système de santé. Cette synthèse évaluative de la recherche vise à fournir un outil de mobilisation des connaissances et des pistes d’action pour mieux répondre aux besoins des populations aînées et pour améliorer l’offre de services. Mots-clés : revue de littérature, aînés francophones, santé, services et politiques de santé, minorité de langue officielle, Canada

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Enjeux de santé des aînés francophones vivant en situation minoritaire : une analyse différenciée selon les sexes - van Kemenade, Solange; Bouchard, Louise; Bergeron, Christian (Reflets, 2015)
La recherche en santé sur les Communautés de langue officielle vivant en situation minoritaire révèle des disparités. Le fait d’être minoritaire dans une société, conjointement avec d’autres déterminants, comme le statut socioéconomique, l’éducation en santé, et le fait de ne pas avoir un soutien social contribuent aux disparités de santé. Dans le contexte du vieillissement plus marqué des populations de langue officielle vivant en situation minoritaire, nous avons examiné la situation des aînés francophones. Pour cela, une analyse secondaire des données issues de l’Enquête sur la santé des collectivités canadiennes (ESCC) a été réalisée. Nous présentons dans cet article, une analyse différenciée de leur situation sociosanitaire selon le sexe et le genre en dressant le portrait des états de santé, des incapacités et des besoins sur le plan des soins de santé. Mots-clés : aînés francophones, situation minoritaire, santé, accès aux soins, services de santé, sexe, langues officielles, Canada, Enquête de santé dans les collectivités canadiennes

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.